Gender features of sensorimotor function in young people with motor asymmetry - Alexander P Romanchuk; Oksana V Guziy; Marina N Glushchenko (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2016)
We have examined 745 healthy young adults aged 21,4±2,6 (including 493 men and 252-women) by using the appliance «Computer movements measurer». Having investigated the sexual features of sensor-motor function taking into account the motor asymmetry we have found that the most likely (p<0,05) differences between the central (switch of central units), subcortical (movement cycle durability) and medullary (reaction time to light) mechanisms of movements appear in left-handed women. The significant results show that there is the polynomial relationship between the left and right hand accuracy measures by taking into account the motor asymmetry in both men and women.